2013
DOI: 10.1152/japplphysiol.01419.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone is elevated following sprint exercise in healthy young men

Abstract: Smith AA, Toone R, Peacock O, Drawer S, Stokes KA, Cook CJ. Dihydrotestosterone is elevated following sprint exercise in healthy young men. J Appl Physiol 114: 1435-1440, 2013. First published March 7, 2013 doi:10.1152/japplphysiol.01419.2012.-Dihydrotestosterone (DHT) exerts both functional and signaling effects extending beyond the effects of testosterone in rodent skeletal muscle. As a primer for investigating the role of DHT in human skeletal muscle function, this study aimed to determine whether circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 43 publications
1
29
2
Order By: Relevance
“…However, another study has demonstrated an increase in serum free testosterone and DHT concentrations immediately after repeated high‐intensity aerobic exercise (consisting of 10 repetitions of 30 s, sprinting at a target load of 150% of the work capacity) in healthy active young men (Smith et al . ). In addition, high‐intensity resistance exercise also increased testosterone concentrations during exercise compared with moderate‐intensity exercise.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, another study has demonstrated an increase in serum free testosterone and DHT concentrations immediately after repeated high‐intensity aerobic exercise (consisting of 10 repetitions of 30 s, sprinting at a target load of 150% of the work capacity) in healthy active young men (Smith et al . ). In addition, high‐intensity resistance exercise also increased testosterone concentrations during exercise compared with moderate‐intensity exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, enzyme expressions related to circulating sex steroid hormone concentrations and muscle steroidogenesis tended to decrease at 3 h after moderate-intensity resistance exercise in our preliminary experiments on healthy young men. However, another study has demonstrated an increase in serum free testosterone and DHT concentrations immediately after repeated high-intensity aerobic exercise (consisting of 10 repetitions of 30 s, sprinting at a target load of 150% of the work capacity) in healthy active young men (Smith et al 2013). In addition, high-intensity resistance exercise also increased testosterone concentrations during exercise compared with moderate-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exercise-induced changes in T are likely to be regulated by several factors such as cycling cadence, 36 heart rate, 37 and perceived exertion. 37 Whilst sprint cycling exercise can reliably increase T concentrations in untrained, active 10,18,38 or highly-trained men, 10,11,36 women do not always exhibit a T response. 21,27 This disparity could be explained by differences in the cycling protocols employed (e.g.…”
Section: T (Pg/ml) Hgs (Kg) Cmj Pp (W) T (Pg/ml) Hgs (Kg) Cmj Pp (W) mentioning
confidence: 99%